From smoking to vaping: the motivation for e-cigarette use at the neurobiological level : a functional magnetic resonance imaging study - Grundinger, Nadja; Andreas, Marike; Lohner, Valerie; Schneider, Sven; Mons, Ute; Vollstädt-Klein, Sabine (Nicotine & tobacco research, 2025)
Electronic cigarettes (e-cigarettes) are considered a potential aid for smoking cessation. This study investigates the neurobiological mechanisms underlying the motivational properties of e-cigarettes compared to tobacco cigarettes and provides insights into their addictive potential and implications for smoking cessation.The study included 47 daily e-cigarette users, the majority of whom were former smokers (n = 43), and 28 nicotine-naïve participants as controls. Among the e-cigarette users, 32 individuals currently used e-cigarettes exclusively, while 15 also used tobacco cigarettes (dual users). Functional magnetic resonance imaging was used to examine anticipatory brain activation to reward-predictive stimuli for money, e-liquid, or tobacco cigarettes, as well as the instrumental response to obtain each reward.Exclusive e-cigarette users demonstrated increased activation in limbic regions, for example, the nucleus accumbens, during the anticipation of e-liquid and money over tobacco cigarettes. Prefrontal regions showed greater activation during the anticipation of money compared to e-liquid or tobacco cigarettes. Dual users showed greater activation for money compared to tobacco cigarettes in the hippocampal limbic system. No significant differences were observed in the anticipation of e-liquid and tobacco cigarettes among dual users.E-cigarettes are perceived as equally rewarding as money, highlighting their addictive potential. Among exclusive e-cigarette users, money and e-liquid have stronger motivational properties than tobacco cigarettes (even among former smokers), suggesting that e-cigarettes may be an effective tool for tobacco cessation. The comparable appeal of e-liquid and tobacco cigarettes among dual users may suggest that a complete switch to e-cigarettes may be more effective for smoking cessation.It is important to understand the motivational properties of e-cigarettes, particularly compared to traditional tobacco products. E-cigarettes with little or no addictive potential might not be effective as a substitute for tobacco cigarettes; however, a high addictive potential would, conversely, pose a risk to nonsmokers. Our data suggest that e-cigarettes have a sufficiently high addictive potential to make them an attractive alternative for smokers, especially if they switch completely from tobacco to e-cigarettes.